Separation and characterisation of detonation nanodiamond by capillary zone electrophoresis. Issue 12 (26th May 2014) - Duffy, Emer; Mitev, Dimitar P.; Nesterenko, Pavel N.; Kazarian, Artaches A.; Paull, Brett; Lapizco‐Encinas, Blanca H.; Davalos, Rafael V.
<x xml:space="preserve">Abstract</x> A new method for the characterisation of purified detonation nanodiamond (DND) using CZE has been developed. The influence of BGE conditions on electrophoretic mobility, peak shape and particle aggregation was investigated, with resultant observations supported by zeta potential approximations and particle size measurements. Sodium tetraborate (pH 9.3), Tris (pH 9.3) and sodium phosphate (pH 7) were used in studying the BGE concentration effect on a commercial source of chemically stabilised DND. The BGE concentration had a strong effect on the stability of DND in suspension. The formation of aggregates of various sizes was observed as BGE concentration increased. The effect of pH on the electromigration of DND was examined using sodium phosphate (pH 8 and 10). The CZE method was subsequently applied to four different DND samples, which had undergone different routes of purification following detonation synthesis. Each sample produced a unique electrophoretic peak or profile in sodium tetraborate buffer (pH 9.3), such that the actual separation of DND samples from different sources could be achieved.